Initiation and perpetuation of rat adjuvant arthritis is inhibited by the anti-CD2 monoclonal antibody (mAb) OX34. Issue 12 (1st December 1997) - Hoffmann, Jörg C; Herklotz, Claudia; Zeidler, Henning; Bayer, Bettina; Rosenthal, Herbert; Westermann, Jürgen
Abstract : OBJECTIVE: The purpose of this study was to investigate the therapeutic potential of the anti-CD2 mAb OX34 first with regard to bone protection in established rat adjuvant arthritis (AA) and secondly with regard to prevention of AA induction. METHODS: Established AA was treated with dexamethasone (1 mg/kg body weight) for two days plus OX34 mAb or control mAb over three days (2 mg and then 1 mg) starting at different time points of the disease. For prevention studies animals were injected as above with mAb before induction of AA. Arthritis score (AS), hindpaw thickness, and body weight were blindly measured three times per week. Flow cytometry and hindpaw radiography were performed at the end of the study (day 29). RESULTS: Treatment of early AA with OX34 mAb combined with dexamethasone but not dexamethasone plus control mAb dramatically suppressed established AA as assessed by AS and hind paw thickness (>65% and >80% reduction, respectively; p < 0.05). Most importantly, early treatment in the course of AA almost completely prevented bone destruction in established AA. When given before AA induction OX34 alone prevented the initiation of arthritis compared with controls (AS reduction 83-95%, p < 0.05). In addition, OX34 plus dexamethasone treatment resulted in depletion of CD4 + T cells but not CD8 + T cells. IL2R + and CD45RC - ('memory') T cells were significantly reduced. CONCLUSIONS: Anti-CD2 mAb treatment prevents AA induction confirming the role of CD4 + T cells in the induction phase of AA. In addition, early OX34 plus dexamethasone treatment resulted in pronounced clinical improvement and joint protection. OX34 treatment therefore inhibits the initiation and the perpetuation of rat AA.